SURVEI TINGKAT KEBUGARAN JASMANI PEMAIN SEPAK BOLA USIA 13-15 TAHUN DI AREMA FOOTBALLACADEMY KOTA MALANG - Afandy, Tsawri; Andiana, Olivia; Kinanti, Rias Gesang (Jurnal Sport Science, 2016)
Abstract :The purpose of this study was to determine the level of physical fitness of soccer players aged 13-15 years in Arema Football Academy by measuring the ability of a test cardiovascular endurance using rockport. This research uses descriptive quantitative research with survey techniques. Rockport test results in 33 subjects showed that there were 13 subjects obtaining the category of